Who Has the Right to Comment on Language Policy in Peru?: A Critical Discourse Analysis - Lovón-Cueva, Marco Antonio; Quispe-Lacma, Alexandra Paola (Íkala, Revista de Lenguaje y Cultura, 2020)
In 2007, the project of the “Law that regulates the use, preservation, development, recovery, promotion and diffusion of the native languages of Peru” generated a series of debates and verbal confrontations inside and outside the parliament; among them, the verbal meeting of the ex-congressmen Martha Hildebrandt, op - ponent of the project, and Maria Sumire, defender of the approval, stood out. Hildebrandt, a linguist by profession, and Sumire, a lawyer by profession and recognized as an indigenous person, gave speeches on self-defense and exclusion. The objective of this article is to analyze the speeches of these congresswomen, which determined the political decision of who had the right to give an opinion on language policy in Peru. The discourses are studied from the critical analysis of the discourse, with a focus on the lexical and discursive strategies employed by the congresswom - en in their statements, because through these their ways of thinking are revealed. The results suggest that, in both cases, although in one more than in the other, hierarchical power relations and discriminatory social practices are reproduced.